2018
DOI: 10.1108/ijmhsc-05-2018-0032
|View full text |Cite
|
Sign up to set email alerts
|

Older migrants’ access to healthcare: a thematic synthesis

Abstract: Purpose The purpose of this paper is to synthesise data from the existent literature on the experiences of non-western older migrants in Europe in accessing and using healthcare services. Design/methodology/approach In total, 1,606 records were reviewed and 12 studies were selected. A thematic synthesis using Thomas and Harden’s approach was conducted. Findings The findings resulted in the three overarching themes: traditional discourses under new circumstances; predisposed vulnerabilities of older migrant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…Arora et al 15 have reported that the older immigrants’ healthcare experiences are affected by aspects of their health literacy, language barriers and differences in health beliefs. Immigrants are a culturally and socioeconomically diverse group, where their experiences of health service use, including dementia care, can vary considerably from the rest of the population 16.…”
Section: Introductionmentioning
confidence: 99%
“…Arora et al 15 have reported that the older immigrants’ healthcare experiences are affected by aspects of their health literacy, language barriers and differences in health beliefs. Immigrants are a culturally and socioeconomically diverse group, where their experiences of health service use, including dementia care, can vary considerably from the rest of the population 16.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have also found low rates of anti-dementia medication prescription and use [ 19 21 ] and a reduced likelihood of entering a long-term-care facility [ 19 , 21 ]. Thus, it seems like elderly immigrants constitute a group that experience special challenges in dementia diagnosis and treatment [ 22 24 ].. A thematic synthesis on older immigrants’ access to health care shows that their experiences of accessing health care are influenced by factors such as health literacy, language barriers and differences in health care beliefs [ 25 ]. As a result, their use of health care services differs from that of natives [ 23 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Older age may heighten these barriers (Khan et al, 2013). According to a thematic synthesis, the barriers facing older immigrants stem from three main areas: a) a different understanding of health, health care and the role of healthcare professionals; b) the traditional discourse of care influencing healthcareseeking behaviour among immigrants; and c) the predisposed vulnerabilities of older immigrants, such as language barriers, low literacy and a lack of information (Arora et al, 2018). Other studies have shown that the intersections of old age, ethnicity, socioeconomic factors and gender have further implications for health and access to healthcare services (Brenner and Clarke, 2016;Northwood et al, 2017;Gee et al, 2003;Goth and Berg, 2011;Villatoro et al, 2017).…”
Section: Introductionmentioning
confidence: 99%